(untitled) (Global Journal of Medical Research, 2020)
Aircraft noise metrics are used to assess airport and heliport noise impacts on host communities. Airports and heliports host communities need to be carried along to contribute to deliberations, understand proposals, and have their views heard on aircraft noise reduction strategies. People can feel disillusioned by noise metrics that are too complex and do not express what residents experience. Selecting the best noise metric is essential if all aviation stakeholders are to engage meaningfully on modalities for aircraft noise reduction. A single global noise metric that would capture all the factors influencing people’s perception of aircraft noise and produce a definitive measure of annoyance is highly desirable, but such does not exist. Some of these noise metrics are simple but do not include subjective factors in their analysis; others that capture both the objective and subjective aspects of aircraft noise effects are complex and difficult to interpret. In selecting a noise metric to use for the measurement of aircraft noise, it is necessary to strike a balance between precision and simplicity. This paper examines the various noise metrics currently used to assess aircraft noise exposure globally and makes a case for equivalent continuous sound level(L eq ) as the best based on the fact that it is easy to understand and communities can easily relate it to their experiences.